2014
DOI: 10.1093/ejo/cju079
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fixed orthodontic treatment using conventional versus metal-injection molding brackets on salivary nickel and chromium levels: a double-blind randomized clinical trial

Abstract: None to declare.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…Studies except one [10] showed that people who had taken dental treatments especially orthodontic appliances for some time, had higher Cr levels in their body tissues than others (see Table 1). …”
Section: Resultsmentioning
confidence: 99%
“…Studies except one [10] showed that people who had taken dental treatments especially orthodontic appliances for some time, had higher Cr levels in their body tissues than others (see Table 1). …”
Section: Resultsmentioning
confidence: 99%
“…They did not observe any significant difference in levels of Ni and chromium before and after the treatment. Amini et al 14 assessed the impact of orthodontic treatment on salivary Ni and chromium levels. From 30 orthodontic patients, saliva samples were collected.…”
Section: Discussionmentioning
confidence: 99%
“…They were also asked not to rinse with fluoridated mouthwashes 24 hrs before the next visit, till after sample collection (38)(39)(40)(41) . The children were directed not to use an oral rinse, not to eat, drink or brush their teeth on the morning of the scheduled visit (36,42) . If any patients were dropped out of the study, they would be replaced with new patients.…”
Section: Ii-in-vivo Studymentioning
confidence: 99%
“…The pH value was recorded after sampling using pH meter, to avoid any pH/CO2 changes (42) . The average of 3 records for each sample was reported.…”
Section: Salivary Ph Level Measurementmentioning
confidence: 99%
See 1 more Smart Citation